Construction site, merry and bright a Christmas lift-the-flap book - Rinker, Sherri Duskey; Ford, AG (San Francisco Chronicle Books, 2021)
"On Christmas Eve, there's just one job left for the big trucks to do--getting their site ready for a festive night of fun! Lift the flaps to reveal what each truck is bringing to the celebration, as they discover that the best Christmas present of all is the gift of being together."--Back cover.
Cover title.
On board pages.
Ages 2-4.
109356
Keywords: Construction equipment -- Juvenile fiction; Christmas stories; Stories in rhyme; Lift-the-flap books -- Specimens; Board books; Christmas fiction; Fiction; Juvenile works; Specimens; Children's stories -- Pictorial works